Comparative Analysis of Web Frameworks for Rapid Development: A Systematic Literature Review - Farid Ullah Qayoumi; Fawad Bikzadl (CV. Proaksara Global Transeduka, 2026)
Selecting the most suitable web framework for rapid development remains a significant challenge for software teams, often leading to increased costs, slower delivery, and technical debt. This paper presents a systematic literature review (SLR) comparing six leading web frameworks React, Vue.js, and Angular for front-end development, alongside Django, Ruby on Rails, and Express.js for back-end development to evaluate their effectiveness for rapid development of Minimum Viable Products (MVPs), Single Page Applications (SPAs), and scalable prototypes. Following the Kitchenham and Charters (2007) SLR guidelines, a systematic search was conducted across IEEE Xplore, ACM Digital Library, and Google Scholar, focusing on 47 empirical studies published between 2015 and 2025 and assessed against five criteria including development speed, learning curve, performance, deployment time, and scalability. Findings reveal that Vue.js and Ruby on Rails offer the fastest initial development times due to gentle learning curves and built-in scaffolding, making them ideal for MVPs. React and Django demonstrate superior scalability and robustness for large-scale, data-intensive applications, while Angular and Express.js excel in enterprise contexts requiring structured architectures and microservice flexibility. No single framework universally outperforms the others; optimal selection depends on project-specific requirements, team expertise, and scalability needs. The study offers evidence-based recommendations to help developers and decision-makers balance rapid development with long-term maintainability.